(untitled) (Research, Society and Development, 2022)
To describe complex probabilistic stratified sampling by clusters, considering difficulties imposed by the COVID-19 pandemic. A sample estimate was carried out for a finite population of schoolchildren aged 5, 12 and 15 years (5062, 5539, 5228); private and rural schools were excluded because of the pandemic and new universe was obtained for 12 and 15 years. It was considered 95% confidence (1.96); 5 and 10% sampling error and 10% non-response rate; previous mean distribution and standard deviation of caries; deff=1.4; outcome prevalences of 50%. Those with the index ages of 12 and 15 years, as recommended by the WHO, enrolled in the selected schools, were evaluated. The samples initially idealized for 12 and 15 years were respectively: 1347 and 2970 for mean caries distribution and 540 and 537 for proportions. The pandemic made initial planning infeasible; the new samples were 1271, 2696, 527 and 528, respectively for 12 and 15 years. The number of students evaluated was 2193, 2084, 233 and 477. The initially idealized planning was not capable of execution, there was a need for a new sample estimate with a change in representativeness. The 12-year-old population evaluated was greater than the estimated, whereas the 15-year-old population was smaller than the estimated.